2022
DOI: 10.3390/brainsci12091138
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Plasticity-Based Signature for Molecular Classification and Prognosis of Lower-Grade Glioma

Abstract: Background: Glioma is one of the major health problems worldwide. Biomarkers for predicting the prognosis of Glioma are still needed. Methods: The transcriptome data and clinic information on Glioma were obtained from the CGGA, TCGA, GDC, and GEO databases. The immune infiltration status in the clusters was compared. The genes with differential expression were identified, and a prognostic model was developed. Several assays were used to detect RPH3A’s role in Glioma cells, including CCK-8, colony formation, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In previous studies, astrocytoma patients demonstrated to experience the worst prognosis compared to other histology patients [ 36 , 37 , 38 ]. In addition, Xu et al and Yang et al found that the highest-risk scores were enriched in astrocytoma patients, but the lowest-risk scores were observed in oligodendroglioma patients [ 39 , 40 ]. These findings were similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, astrocytoma patients demonstrated to experience the worst prognosis compared to other histology patients [ 36 , 37 , 38 ]. In addition, Xu et al and Yang et al found that the highest-risk scores were enriched in astrocytoma patients, but the lowest-risk scores were observed in oligodendroglioma patients [ 39 , 40 ]. These findings were similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Data for the study were collected from the TCGA database 15 ( https://www.cancer.gov/ccg/ ). We downloaded the data of glioma patients (n = 706) from TCGA ( http://portal.gdc.cancer.gov ) to analyze the RNA sequencing and patient information, and we used a transfer tool that was provided by GDC to capture the statistics 16 . In addition, we obtained data from the CGGA database ( http://www.cgga.org.cn/ ) to download PSMB2 expression and clinical data of glioma patients, and analyze the relationship between PSMB2 and patient prognosis.…”
Section: Methodsmentioning
confidence: 99%
“…Further experiments demonstrated that downregulation of PCBP1 increased the sensitivity of head and neck cancer to ferroptosis (Lee et al, 2022). In addition, many other researchers found that radiotherapy might affect ferroptosis by mediating the expression of iron metabolism-related proteins such as iron ion-related carriers like ferritin, FPN, regulatory iron regulators, membrane iron transport auxiliary protein (Hephaestin) and copper cyanobacteria by mediating hypoxiainducible factor 1α (HIF-1α) or HIF-2α (Shah et al, 2009;Singhal et al, 2021;Yang et al, 2022). Therefore, we consider that the regulation of intracellular iron ion content by radiation to cause iron overload to enhance ferroptosis sensitivity in tumor cells is expected to be an effective way to enhance radiosensitivity.…”
Section: Radiotherapy Might Affect Ferroptosis Through Iron Metabolismmentioning
confidence: 99%
“…Meanwhile, radiation is able to significantly increase the staining of C11-BODIPY, lipid peroxidation markers MDA and 4-HNE in cancer cells and tumor samples, indicating that radiation induces lipid peroxidation (Lei et al, 2020a;Zhang et al, 2021a;Zhou et al, 2022). Similarly, irradiated cells exhibit increased expression of the ferroptosis marker gene prostaglandin endoperoxide synthase 2 (PTGS2) (Busato et al, 2022;Yang et al, 2022). Furthermore, Seiji Torii et al shows that knockdown of Arachidonate 15-Lipoxygenase (ALOX15) decreases erastin-induced and RSL3-induced cellular ferroptosis, on the contrary exogenous overexpression of ALOX15 enhances the effects of these compounds.…”
Section: Radiotherapy Induces Ferroptosis By Promoting Lipid Peroxida...mentioning
confidence: 99%